2011
DOI: 10.1021/ac102932d
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-Functionalized Porous Polymer Monolith Detection Elements for Surface-Enhanced Raman Scattering

Abstract: The use of porous polymer monoliths functionalized with silver nanoparticles is introduced in this work for high-sensitivity surface-enhanced Raman scattering (SERS) detection. Preparation of the SERS detection elements is a simple process comprising the synthesis of a discrete polymer monolith section within a silica capillary, followed by physically trapping silver nanoparticle aggregates within the monolith matrix. A SERS detection limit of 220 fmol for Rhodamine 6G (R6G) is demonstrated, with excellent sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
91
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(94 citation statements)
references
References 51 publications
(95 reference statements)
3
91
0
Order By: Relevance
“…Generally, the sensing analysis has been done by directly mixing the silver colloids with the analyte solution [23]. Therefore, silver is considered to be a single use system as opposed to multiple uses for a silver thin film [24]. The silver thin film can easily be washed to remove the analyte from the surface to allow a second or potentially repeated analysis and this result alternatively helps to prove the repeatability of the sensing system.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the sensing analysis has been done by directly mixing the silver colloids with the analyte solution [23]. Therefore, silver is considered to be a single use system as opposed to multiple uses for a silver thin film [24]. The silver thin film can easily be washed to remove the analyte from the surface to allow a second or potentially repeated analysis and this result alternatively helps to prove the repeatability of the sensing system.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles were recently explored to functionalize the monoliths with specific selectivity. The approaches are divided into two categories: (i) direct encapsulation of nanoparticles into the monolith in the process of polymerization [21][22][23] and (ii) modification of surface with nanoparticles after monolith formation [24][25][26][27][28][29][30]. The latter approach results in a remarkable increase in the effective surface area of monolith, which was successfully applied for CEC and cLC separation, and solid-phase extraction as well.…”
Section: Introductionmentioning
confidence: 99%
“…The success has been attributed to the exceptional convective mass flow of fluids in monoliths, the capacity of the composite structure to direct metal nanostructures, the tuneable pore size, and high surface area enabling an enhanced interaction between target and SERS active surfaces [104,105]. In light of this, an AgNP-modified monolithic substrate for SERS was developed by Liu, White, and DeVoe [104] for a label-free detection of peptide bradykinin and cytochrome c. In addition, it was shown from their analysis that the copolymerisation of AgNP with acrylic-based polymeric monoliths synthesised by means of UV-radiation yielded low sensitivity in the detection of Rhodamine 6G (R6G dye) as compared to an AgNP-surface modified hydrophobic BMA-co-EDMA and GMA-co-SR454. Notably, the latter had a higher sensitivity towards R6G amongst the three set of analysis [104].…”
Section: Silver Nanoparticles (Agnps)mentioning
confidence: 99%
“…In light of this, an AgNP-modified monolithic substrate for SERS was developed by Liu, White, and DeVoe [104] for a label-free detection of peptide bradykinin and cytochrome c. In addition, it was shown from their analysis that the copolymerisation of AgNP with acrylic-based polymeric monoliths synthesised by means of UV-radiation yielded low sensitivity in the detection of Rhodamine 6G (R6G dye) as compared to an AgNP-surface modified hydrophobic BMA-co-EDMA and GMA-co-SR454. Notably, the latter had a higher sensitivity towards R6G amongst the three set of analysis [104]. Nevertheless, Navarro-Pascual-Ahuir, Lerma-García, Ramis-Ramos, Simó-Alfonso, and Herrero-Martínez [30] demonstrated that doping of AgNP into LMA-monoliths via copolymerisation or surface modification both led to changes in the chromatographic properties, relative to an unmodified LMA-monolith.…”
Section: Silver Nanoparticles (Agnps)mentioning
confidence: 99%